2017
DOI: 10.4014/jmb.1605.05023
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Stable Reference Genes for Real-Time Quantitative PCR Analysis in Edwardsiella tarda

Abstract: is a gram-negative pathogenic bacterium in aquaculture that can cause hemorrhagic septicemia in fish. Many secreted proteins have already been identified as virulent factors of . Moreover, since virulent phenotypes are based on the expression regulation of virulent genes, understanding the expression profile of virulent genes is important. A quantitative RT-PCR is one of the preferred methods for determining different gene expressions. However, this requires the selection of a stable reference gene in, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Thus, in this study, rrs would be used for normalization to validate the selection result in 12% ethanol. Furthermore, in order to neutralize the impact of the high abundance of rrs , the templates for rrs should be diluted more times than the samples for the other genes in RT-qPCR analysis, however the different dilution ratios can lead to more human errors (Sun et al, 2016 ). Thus, in each experiment, three independent biological replicates and three technical replicates were required at least.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study, rrs would be used for normalization to validate the selection result in 12% ethanol. Furthermore, in order to neutralize the impact of the high abundance of rrs , the templates for rrs should be diluted more times than the samples for the other genes in RT-qPCR analysis, however the different dilution ratios can lead to more human errors (Sun et al, 2016 ). Thus, in each experiment, three independent biological replicates and three technical replicates were required at least.…”
Section: Discussionmentioning
confidence: 99%
“…GyrA is responsible for DNA cleavage and ligation, and GyrB contains ATP-binding sites [46]. DNA gyrase subunits have been recommended as reference genes in several bacterium species, including Oenococcus oeni [47], Shewanella psychrophila [36], Dwardsiella tarda [48], Xanthomonas fragariae [42], Bacillus velezensis [49], Corynebacterium pseudotuberculosis [19] and Herbaspirillum rubrisubalbicans [50].…”
Section: Discussionmentioning
confidence: 99%
“…A number of housekeeping genes such as 16S ribosomal RNA (16S rRNA), ribosome protein L13 (rbL13), RNA polymerase factor, DNA polymerase factor and elongation factor have been used as reference genes in different expression profiling studies in bacteria [11][12][13][14]. However, it is reported that the expression of housekeeping genes may vary among various species and different experimental conditions.…”
Section: Introductionmentioning
confidence: 99%